Analysis of the causal relationship between direct taxes and GDP in Syria (Standard Study oF 1991-2018) (Journal of Hama University, 2021)
The study aimed to study and determine the nature of the relationship between direct taxes and the gross domestic product in Syria during the period (1991-2017), where data related to time series were obtained based on the figures issued by the Ministry of Finance and the Syrian statistical group, and the study followed the descriptive approach using the method of Standard statistical analysis in order to analyze the relationship between direct taxes and GDP using Eviews10 program, and the study used unit root tests, and relied on the methodology of self-regression and dynamic analysis by analyzing the components of variance and the immediate response function using the VAR model and the causation test of Granger and Toda's methodology to find out the existence and direction of the relationship The results of the unit root tests revealed the instability of the variables in their levels, and Granger's results indicated a one-way relationship from direct taxes to GDP in the short term, while a long-term two-way relationship was found between the two variables according to Toda's statistic, and it was observed by estimating the regression vector. The self has a significant effect for each of the two variables on each other, either The results of the analysis of shocks indicated the presence   of   negative effects between each of the two variables, and the study recommendedthe necessity of reducing direct tax rates in order to enhance the ability of individuals and companies to invest and form private capital that contributes to enhancing the gross domestic product